Phylogenetic distribution and structural analyses of cyanobacterial glutaredoxins (Grxs). (February 2020) - Mondal, Soumila; Kumar, Vinod; Singh, Shailendra P.
Graphical abstract: Highlights: Four classes of Grxs were found in 167 cyanobacteria based on phylogenetic analyses. Two novel active site motifs (CPFS and CPFC) were identified in class VI Grxs for the first time. Active site and putative glutathione binding site are composed of uncharged amino acids. Protein-ligand interaction analysis identified novel glutathione binding sites. Grx encoding genes of S. elongatus PCC 7942 are regulated by high PAR, UVR and salinity. Abstract: Glutaredoxins (Grxs), the oxidoreductase proteins, are involved in several cellular processes, including maintenance of cellular redox potential and iron-sulfur homeostasis. The analysis of 503 amino acid sequences from 167 cyanobacterial species led to the identification of four classes of cyanobacterial Grxs, i.e., class I, II, V, and VI Grxs. Class III and IV Grxs were absent in cyanobacteria. Class I and II Grxs are single module oxidoreductase while class V and VI Grxs are multimodular proteins having additional modules at their C-terminal and N-terminal end, respectively. Furthermore, class VI Grxs were exclusively present in marine cyanobacteria. We also report the identification of class VI Grxs with two novel active site motif compositions. Detailed phylogenetic analysis of all four classes of Grxs revealed the presence of several subgroups within each class of Grx having variable dithiol and/or monothiol catalytic active site motif and putative glutathione binding sites. However, class II Grxs possess CGFS-type highly conserved monothiol catalytic active site motif. Sequence analysis confirmed the highly diverse nature of Grx proteins in terms of their amino acid composition; though, sequence diversity does not affect the overall 3D structure of cyanobacterial Grxs. The active site residues and putative GSH binding residues are uncharged amino acids which are present on the surface of the protein. Additionally, the presence of hydrophilic residues at the surface of Grxs confirms their solubility. Protein-ligand interaction analysis identified novel glutathione binding sites on Grxs. Regulation of Grxs encoding genes expression by light quality and quantity as well as salinity suggests their role in determining the fitness of organisms under abiotic factors.